The Semitransparent Photovoltaic Films for Mediterranean Greenhouse: A New Sustainable Technology. (20th December 2012) - Marucci, Alvaro; Monarca, Danilo; Cecchini, Massimo; Colantoni, Andrea; Manzo, Alberto; Cappuccini, Andrea
Abstract : Mediterranean countries offer very favorable climatic conditions for growing plants in a protected environment: as a matter of fact, the high solar radiation allows the use of greenhouses with simple structures, covered with plastic film and without fixed installations for winter heating. They are called "Mediterranean greenhouses" and are totally different from those in Central and Northern Europe. In the photovoltaic greenhouses, the cover on the pitch facing south is usually replaced by very opaque panels. However, this solution compromises the possibility to grow plants in covered and protected environments since solar radiation availability is limited and strongly nonuniform. In order to overcome this problem, semitransparent photovoltaic materials can be used to let the solar energy, necessary for plant growth, pass into the green house. The aim of this research is to analyze the radiometric properties of innovative semitransparent flexible photovoltaic materials in order to evaluate their performances in comparison with materials commonly used in the coverage of the greenhouses. Particular attention is paid to the transmittance of these materials in the visible range and in the long wave infrared for the achievement of greenhouse effect.